2023
DOI: 10.3390/ijms24076605
|View full text |Cite
|
Sign up to set email alerts
|

Short Photoperiod-Dependent Enrichment of Akkermansia spec. as the Major Change in the Intestinal Microbiome of Djungarian Hamsters (Phodopus sungorus)

Abstract: The Djungarian hamster (Phodopus sungorus) is a prominent model organism for seasonal acclimatization, showing drastic whole-body physiological adjustments to an energetically challenging environment, which are considered to also involve the gut microbiome. Fecal samples of hamsters in long photoperiod and again after twelve weeks in short photoperiod were analyzed by 16S-rRNA sequencing to evaluate seasonal changes in the respective gut microbiomes. In both photoperiods, the overall composition was stable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In Alzheimer's disease mouse models, the development of symptoms is accompanied by a reduction in A. muciniphila in the gut microbiome [56]. A marker-like characteristic of microbiomes in obesity is a low abundance of A. muciniphila [57], and upon weight loss, a restoration occurs, which is also the case in environmentally induced metabolic switches in animals [96]. A. muciniphila supplementation can be of therapeutic relevance in reducing body weight in obese humans [56].…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer's disease mouse models, the development of symptoms is accompanied by a reduction in A. muciniphila in the gut microbiome [56]. A marker-like characteristic of microbiomes in obesity is a low abundance of A. muciniphila [57], and upon weight loss, a restoration occurs, which is also the case in environmentally induced metabolic switches in animals [96]. A. muciniphila supplementation can be of therapeutic relevance in reducing body weight in obese humans [56].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study in chickens revealed that the chicks in 12L:12D group possess genera that are typically associated with healthy guts, whereas the chicks in 23L:1D group possess genera that are typically found in diseased guts ( Hieke et al, 2019 ). In zebrafish, Djungarian hamsters, and Siberian hamsters, it was also found that the microbial communities can be altered by photoperiod ( Bailey et al, 2010 ; Basili et al, 2020 ; Kissmann et al, 2023 ). The diversity and variety of gut microbiota affect inflammation through the activation of NLRP3 inflammasomes and the release of inflammatory cytokines, conversely, the composition of the gut microbiota can be influenced by the activation of NLRP3 inflammasomes ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“…More and more evidence suggests that the imbalance of the gut microbiota is related to the development of intestinal inflammation [ 9 , 10 , 11 ]. Prolonging exposure to light can alter the composition of the gut microbiota in animals [ 12 , 13 , 14 , 15 ]. Interestingly, previous research found that the chicks in a 12L:12D group possessed genera that are typically associated with healthy guts, whereas the chicks in a 23L:1D group possessed genera that are typically found in diseased guts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%